Synergistic Effect of Excited State Property and Aggregation Characteristic of Organic Semiconductor on Efficient Hole‐Transportation in Perovskite Device. (8th October 2020) - Jo, Bonghyun; Park, Hansol; Kamaraj, Eswaran; Lee, Sewook; Jung, Bumho; Somasundaram, Sivaraman; Jeon, Gyeong G.; Lee, Kyu‐Tae; Kim, Namdoo; Kim, Jong H.; Kim, Bong‐Gi; Ahn, Tae Kyu; et al.
Abstract: Intrinsic characteristics of organic semiconductor‐based hole transport materials (HTMs) such as facile synthesizability, energy level tunability, and charge transport capability have been highlighted as crucial factors determining the performances of perovskite photovoltaic (PV) cells. However, their properties in the excited state have not been actively studied, although PVs are operated under solar illumination. Here, the characteristics of organic HTMs in their excited state such as transition dipole moment can be a decisive factor that can improve built‐in potential of PVs, consequently enhancing their charge extraction property as well as reducing carrier recombination. Moreover, the aggregation property of organic semiconductors, which has been an essential factor for high‐performance organic HTMs to improve their carrier transport property, can induce a synergistic effect with their excited state property for the high‐efficiency perovskite PVs. Additionally, it is also confirmed that their optical bandgaps, manipulated to have their absorption in the UV region, are beneficial to block UV light that degrades the quality of perovskite, consequently improving the stability of perovskite PV in p–i–n configuration. As a proof‐of‐concept, a model system, composed of triarylamine and imidazole‐based organic HTMs, is designed, and it is believed that this strategy paves a way toward high‐performance and stable perovskite PV devices. Abstract : The excited state characteristics of organic hole transport materials in perovskite photovoltaics (PVs), such as transition dipole moment, is confirmed to be a critical factor in improving the built‐in potential of devices for efficient charge extraction along with reduced carrier recombination. Moreover, the aggregation property of the organic semiconductor can have a synergistic effect with its excited state property for high‐efficiency perovskite PVs.